A systematic review and thematic synthesis of research on school leadership in the Republic of Ireland: 2008–2018. Issue 6 (29th May 2019) - Murphy, Gavin
Abstract : Purpose: The purpose of this paper is to review and generate themes evident in research on primary and post-primary (secondary) school leadership in the Republic of Ireland (Ireland) from 2008 to 2018. Design/methodology/approach: This paper follows the steps of a systematic review and thematic synthesis. Findings: Following the review, six themes are identified and described, summarising the most current school leadership research in Ireland. Practical implications: Potential future directions of research are identified. Originality/value: No review of research on school leadership in Ireland is currently available and this is timely given the policy context's recent focus on school leadership. The steps taken to conduct the review are clearly outlined.